Fenomena Pengguna Second Account di Instagram dalam Aktualisasi Diri pada Remaja (Studi Kasus Fenomenologi di Wilayah Jakarta Timur) - Yuntaffiani, Ghaniya; Erlangga, Christopher Yudha (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study examines the phenomenon of teenagers using a second account on Instagram as a means of supporting self-actualization in the digital era. A second account, or secondary account, provides a private space for teenagers to share personal content, express feelings, and explore their identity without the social pressures that often arise on the main account. Using a qualitative phenomenological approach, this study explores the subjective experiences of teenagers in using a second account as a tool to display a more honest and liberating self-image. The study shows that a second account not only functions as protection from social pressure, but also becomes a useful medium for building self-confidence, building closer relationships with small social circles, and exploring various aspects of one's identity. In a broader context, this phenomenon reflects changes in the behavior of social media users who increasingly need private space in the digital world. This study is expected to enrich the literature on the role of social media in shaping personal identity and become a reference for further research on the behavior of digital platform users.